Enhancement of Silymarin Anti-fibrotic Effects by Complexation With Hydroxypropyl (HPBCD) and Randomly Methylated (RAMEB) β-Cyclodextrins in a Mouse Model of Liver Fibrosis - Sami Gharbia; Cornel Balta; Hildegard Herman; Marcel Rosu; Judit Váradi; Ildikó Bácskay; Miklós Vecsernyés; Szilvia Gyöngyösi; Ferenc Fenyvesi; Sorina N. Voicu; Miruna S. Stan; Roxana E. Cristian; et al. (Frontiers Media S.A., 2018)
Silymarin (Sy) shows limited water solubility and poor oral bioavailability. Water-soluble hydroxypropyl (HPBCD) and randomly methylated (RAMEB) β-cyclodextrins were designed to enhance anti-fibrotic efficiency of silymarin in CCl4-induced liver fibrosis in mice. Experimental fibrosis was induced by intraperitoneal injection with 2 ml/kg CCl4 (20% v/v) twice a week, for 7 weeks. Mice were orally treated with 50 mg/kg of Sy-HPBCD, Sy-RAMEB and free silymarin. For assessment of the spontaneous reversion of fibrosis, CCl4 treated animals were investigated after 2 weeks of recovery time. The CCl4 administration increased hepatic oxidative stress, augmented the expression of transforming growth factor-β1 (TGF-β1) and Smad 2/3, and decreased Smad 7 expression. Furthermore, increased α-smooth muscle actin (α-SMA) expression indicated activation of hepatic stellate cells (HSCs), while up-regulation of collagen I (Col I) and matrix metalloproteinases (MMPs) expression led to an altered extracellular matrix enriched in collagen, confirmed as well by trichrome staining and electron microscopy analysis. Treatment with Sy-HPBCD and Sy-RAMEB significantly reduced liver injury, attenuating oxidative stress, restoring antioxidant balance in the hepatic tissue, and significantly decreasing collagen deposits in the liver. The levels of pro-fibrogenic markers' expression were also significantly down-regulated, whereas in the group for spontaneous regression of fibrosis, they remained significantly higher, even at 2 weeks after CCl4 administration was discontinued. The recovery was significantly lower for free silymarin group compared to silymarin/β cyclodextrins co-treatments. Sy-HPBCD was found to be the most potent anti-fibrotic complex. We demonstrated that Sy-HPBCD and Sy-RAMEB complexes decreased extracellular matrix accumulation by inhibiting HSC activation and diminished the oxidative damage. This might occur via the inhibition of TGF-β1/Smad signal transduction and MMP/tissue inhibitor of MMPs (TIMP) rebalance, by blocking the synthesis of Col I and decreasing collagen deposition. These results suggest that complexation of silymarin with HPBCD or RAMEB represent viable options for the its oral delivery, of the flavonoid as a potential therapeutic entity candidate, with applications in the treatment of liver fibrosis.